(untitled) (Archive of Conferences, 2020)
The object of international law is international, more precisely, interstate relations, which, in essence, go beyond the jurisdiction of a particular state. Unlike domestic law, there are no legislatures responsible for the development and enforcement of international law. The main subjects of international law are states. The norms of international law that arise by mutual consent express the agreed will of states. This is the peculiarity of international law. Various international treaties, agreements, treaties, conventions, declarations, and UN documents are the normative basis of international law. The following article will discuss subjects of international law and their obligations.